2012
DOI: 10.1002/lt.23532
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early graft survival after pediatric liver transplantation

Abstract: The objective of this study was to identify peritransplant predictors of early graft survival and posttransplant parameters that could be used to predict early graft outcomes after pediatric liver transplantation (PLT). The response of children to liver dysfunction after liver transplantation (LT) is poor. No data have been reported for early predictors of poor graft survival, which would potentially be valuable for rescuing children at risk after LT. A retrospective cohort study of 422 PLT procedures performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is not unprecedented as it has been recently reported that postoperative model for end-stage liver disease score was better than PST-based models to predict early posttransplant mortality. 24 In addition, whereas high PST values were associated with lower early graft and patient survival in several studies, [25][26][27][28] this result remains controversial. 25 PST had a limited influence of LOS.…”
Section: Interpretation With Reference To Other Studiesmentioning
confidence: 95%
“…This is not unprecedented as it has been recently reported that postoperative model for end-stage liver disease score was better than PST-based models to predict early posttransplant mortality. 24 In addition, whereas high PST values were associated with lower early graft and patient survival in several studies, [25][26][27][28] this result remains controversial. 25 PST had a limited influence of LOS.…”
Section: Interpretation With Reference To Other Studiesmentioning
confidence: 95%
“…Liver cell transplantation in humans has proved to be feasible and safe, and the majority of the cases demonstrated clinical improvements over time. However, it has not yet achieved sustainable benefits for patients due to the poor repopulating capacity of engrafted cells [ 11 , 47 , 48 ]. Possible reasons for the unsustainable long-term outcome of transplanted cells may be insufficient cell translocation through the endothelial cell barrier, insufficient cell engraftment into the liver plates and destruction of the engrafted cells by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The Olthoff criteria used for the definition of EAD have been shown to adequately predict graft survival in pediatric liver transplant recipients [33]. Indeed, in our population, 3-month graft survival was 24% lower if EAD occurred.…”
Section: Discussionmentioning
confidence: 63%